Development of Inflow Performance Relationship Equations Based on The Vogel and Eickmeier Methods - Napitupulu, Welman Daud; Destarandra, Octa Rifallah; Louhenapessy, Stevy C.; Manurung, Wulan Indah Syari; Khadaffilam, Muhammad Rizqidina; Wicaksono, Abieza Septiawan (Penerbitan Universitas Trisakti, 2026)
The conventional Vogel Inflow Performance Relationship (IPR) method, when applied to oil wells, exhibits substantial discrepancies relative to actual production data. Consequently, the Development of a more representative model is imperative to enhance the precision of well performance predictions. The objective of this study is to develop an IPR equation based on the Vogel and Eickmeier methods that better aligns with the characteristics of the reservoir under study. Accurate IPR evaluation is imperative for predicting oil production rates in response to variations in well bottomhole pressure, thereby supporting decision-making in production planning, flow-rate optimization, and field-development feasibility studies. The analysis results indicate that developing an IPR equation based on the Vogel and Eickmeier methods can reduce forecasting errors and accurately represent the relationship between oil production rates and well bottom pressure. Consequently, the developed IPR model can serve as a tool to aid in production management and further Development planning.